TRANSLATING PROCEDURES ON IPHONE 7 PLUS USER GUIDE - Yolanda Novita Silaban; mailani ifanlia clara; azasmin ndruru; wira cahyani laoli; sumiati sirait (elt, 2019)
This thesis is talking about Translating Procedures on Iphone 7 Plus User Guide. The data were analyzed by using Vinay and Darbelnet’s translation theory. This theory divides the translation method into two parts : (1) literal translation (2) oblique translation which are further subdivided into seven parts, (a) borrowing, (b) literal translation, (c) transposition, (d) modulation, (e) reduction, and (f) adaptation. Nowadays, translation has an important role especially for people in Indonesia. A qualitative descriptive method was employed to analyze the data by referring to two theories of translating procedures proposed by Newmark (1988) and Vinay & Darbelnet (2000) and a number of theories of quality of translation: Barnwell (1980, in Larson 1984), Larson (1984), etc. The result of data analysis shows that there are six translation procedures found in the text: Borrowing (54 items or 27%), Calque Translation (12 items or 6%), Literal Translation (31 items or 15.5%), Transposition (42 items or 21%), Adaptation (43 items or 21.5%), and Reduction (18 items or 9%). Moreover, the data analysis result also reveals that the quality of translation is good based on the percentages of acceptable translation (94%) and unacceptable translation (6%). In the words level there are 76 acceptable items and 10 unacceptable items. Next, in the phrases level there are 60 acceptable items and 2 unacceptable items. Then, in the sentences level there are 52 acceptable items and no unacceptable items. Furthermore, the total acceptable items in the text are 188 items (76 words, 60 phrases, and 52 sentences) or 94 % from 200 items and for the unacceptable items there are 12 items (10 words, 2 phrases, and 0 sentences) or 6% from 200 items.